The Role of Parents to Students' Learning Process and Its Influence on Learning Outcome in Cognitive Aspect: A Study at Urban Elementary School - Dian Andesta Bujuri; Khoerunnisha; Tutut Handayani; Fitri Oviyanti; Ayu Nur Shawmi; Masnun Baiti (International Journal of Elementary Education, 2024)
This research refutes previous research that not all parents in urban areas who are busy working do not play a role in the students' learning process. This research describes the role of parents in the student learning process and measures their influence on student learning outcomes in elementary schools. The research method used is mixed method. Qualitative data was obtained by conducting interviews with parents, teachers and students. Meanwhile, quantitative data was obtained through questionnaires and student learning outcomes in cognitive aspects. The sample in this research was 5th grade students at State Elementary School, totaling 45 students. The questionnaire in this research was tested using validity and reliability tests. Meanwhile, to test the influence of the role of parents on student learning outcomes using the T test. Based on the results of the t-test calculation, obtained tcount of 3.453 > ttable value of 1.681 with a significance level of 5% or 0.05. The significant level of the parental role variable is 0.001 < the significant level value of 0.05, which means that there is a significant influence between the role of parents on student learning outcomes. The coefficient of determination value is 0.217. However, this research found that there are other factors besides the role of parents. Referring to the coefficient of determination or R square, it is 0.217 or equal to 21.7%. This figure means that the role of parents has an influence of 21.7%, while 78.3% is influenced by other variables outside the variables studied.